Sensing Arrays Constructed from Nanoparticle Thin Films and Interdigitated Microelectrodes - Wang, Lingyan (Molecular Diversity Preservation International (MDPI), 2006)
This paper describes the results of a study of a few design parameters influencing the performance of sensor arrays constructed from nanostructured thin films and interdigitated microelectrodes (IMEs). The nanostructured thin films on the IME devices were prepared from nonanedithiol (NDT) and mercaptoundecanoic acid (MUA) linked assemblies of 2-nm sized gold nanoparticles. The sensor array data in response to volatile organic compounds were collected and analyzed using fractional factorial experimental design and analysis of variance for understanding effects of the design parameters on the sensitivity. While the smaller value for the microelectrode space, width, and length generally led to higher response sensitivity, a strong dependence on the nature of the nanostructured thin films was found. The microelectrode space was the most important design parameter for NDT-based thin films. However, the microelectrode space, width, and length were found to play almost equally important roles for MUA-based thin films. The principal component analysis results for classification performances of the arrays consisting of a set of thin films have demonstrated the possibility of optimizing sensor arrays by appropriate selections of microelectrode parameters and nanostructured sensing films.